Some characteristics on the generative power of weighted one-sided splicing systems - Yee, Sian Gang; Wan, Heng Fong; Sarmin, Nor Haniza; Turaev, Sherzod (American Institute of Physics, 2015)
A splicing system is a formal model for DNA based computation using the recombinant behavior of DNA molecules in the presence of enzymes and ligase. Since it was introduced in 1987, several variants with different restrictions and extensions have been developed. In this paper, a restricted variant of splicing systems, called one-sided splicing systems have been studied. The generative capacity of one-sided splicing systems with the presence of weight is investigated. We have also shown that the use of different weighting spaces and weight operations results in weighted one-sided splicing systems with different generative capacities.